Ritter Syndrome Mimicking Drug Eruption - ÜLGEN ZENGİN, SENİYYE; Idin, Kadir; UYSAL, HARUN; ÜLGEN ZENGİN, SENİYYE; UYSAL, HARUN; Alver, Selcuk; SALİHOĞLU, Ziya (My University, 2015)
Ritter syndrome mimicking drug eruption staphylococcal scalded skin syndrome is a rare fatal condition in adults with erythematous and bullous lesions. With appropriate and immediate therapy, mortality decreases by 5%; a differential diagnosis is necessary. In this case, we report Ritter syndrome mimicking drug eruption.
Keywords: Ritter Syndrome; Staphylococcal scalded skin syndrome; intensive care